Pengaruh Kualitas Sumberdaya Manusia Terhadap Pertumbuhan Ekonomi Kabupaten Mimika - Manduapessy, Rulan; Sutrisno, Irwan (STIE Jambatan Bulan, 2021)
The purpose of this study was to determine the effect of the quality of human resources on economic growth in Mimika Regency. The method used is the associative method, to determine the relationship or influence. The analytical tool used is simple linear regression. The results of the analysis show that there is no relationship or influence of the quality of human resources on economic growth in Mimika Regency.